2013
DOI: 10.1210/jc.2012-3952
|View full text |Cite
|
Sign up to set email alerts
|

Thyroglobulin Is a Sensitive Measure of Both Deficient and Excess Iodine Intakes in Children and Indicates No Adverse Effects on Thyroid Function in the UIC Range of 100–299 μg/L: A UNICEF/ICCIDD Study Group Report

Abstract: In school-aged children, 1) Tg is a sensitive indicator of both low and excess iodine intake; 2) a median Tg of <13 μg/L and/or <3% of Tg values >40 μg/L indicates iodine sufficiency in the population; 3) the acceptable range of median UIC in monitoring iodized salt programs could be widened to a single category of sufficient iodine intake from 100 to 299 μg/L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
153
2
20

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 194 publications
(186 citation statements)
references
References 29 publications
11
153
2
20
Order By: Relevance
“…However, when prolonged excess iodine intake occurs, Tg could increase because the thyroid gland fails to escape from the Wolff-Chaikoff effect (88). Nonetheless, close examination of data reported by Zimmermann et al (41) suggests that the relationship between UIC and Tg is highly variable. It is not known, however, how much of this variability is associated with UIC and/or Tg because a single UIC can be confounded by the hydration status, dietary intake, and diurnal variation (4).…”
Section: Childrenmentioning
confidence: 91%
See 4 more Smart Citations
“…However, when prolonged excess iodine intake occurs, Tg could increase because the thyroid gland fails to escape from the Wolff-Chaikoff effect (88). Nonetheless, close examination of data reported by Zimmermann et al (41) suggests that the relationship between UIC and Tg is highly variable. It is not known, however, how much of this variability is associated with UIC and/or Tg because a single UIC can be confounded by the hydration status, dietary intake, and diurnal variation (4).…”
Section: Childrenmentioning
confidence: 91%
“…It is suggested that this is because current Tg assays are unable to identify the heterogeneity of Tg epitopes (52,62). Of 34 articles measuring Tg (Table 1), only four (40,41,63,64) used Tg CRM-457 as an external quality control.…”
Section: Methods To Measure Tg Concentrationmentioning
confidence: 99%
See 3 more Smart Citations